2021
DOI: 10.1016/j.maturitas.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and resilience in peri- and postmenopausal women during Covid-19 confinement

Abstract: Highlights Physical activity and sexual activity are associated with high quality of life and high levels of resilience. The use of antidepressants is associated with poor quality of life and low levels of resilience. Quality of life was greater among women who lived with others during Covid-19 confinement. Covid-19 status is not an independent factor for quality of life or resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
1
16
1
2
Order By: Relevance
“…This challenges popular and arguable paternalistic assumptions around menopausal women as in need of the care or help from policy and legislation [ 9 , 17 ]. Concepts and models of psychological resilience to menopausal difficulties are emerging as explanations for the epidemiology of symptoms [ 30 ]. A more asset-based approach to menopause and work research might inform which women cope best with which symptoms and why.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This challenges popular and arguable paternalistic assumptions around menopausal women as in need of the care or help from policy and legislation [ 9 , 17 ]. Concepts and models of psychological resilience to menopausal difficulties are emerging as explanations for the epidemiology of symptoms [ 30 ]. A more asset-based approach to menopause and work research might inform which women cope best with which symptoms and why.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, this review found that women in casual work attributed their menopausal symptoms and their difficulties in managing them not to their inadequate or unfair working conditions, but to their broader life circumstances [ 21 23 ]. Amongst the multiple everyday challenges these women navigated, work was not necessarily a major part of life, and therefore not necessarily a major stress factor [ 21 , 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The teaching, anxiety and preparedness section questions were generated to measure the level of preparedness the academic professionals had developed during the quarantine and to measure the levels of anxiety the adaptation to new methods of teaching have produced, and the return to a physical classroom using 4 questions and results were given the following classifications: Absent = 0-4, Mild = 5-8, Moderate = 9-12. Finally, we made an adaptation for the present study using five questions and we gave results using the following classifications: Very low (0-4), Low (5-8), Normal (9-12), High (13)(14)(15)(16), and Very high (17)(18)(19)(20). We evaluated the final version of the full questionnaire for internal consistency using Cronbach alpha (value > 0.9) to ensure reliability.…”
Section: Methodsmentioning
confidence: 99%
“…We can also define resilience as a dynamic adaptative process that helps maintain a healthy psychological state. We can even say that individuals with high resilience have become mentally stronger because of adverse conditions ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Entre as consequências que a pandemia trouxe para a população destacam-se o aumento do sedentarismo, percepção de piora na capacidade física, na saúde e, consequentemente, a redução da qualidade de vida [8][9][10][11] . O quadro clínico pode ser ainda mais grave nos indivíduos que dependem exclusivamente do sistema público de saúde para o tratamento das doenças, incluindo os pacientes com DAP.…”
Section: Introductionunclassified